Cert Prep: Unity Certified Associate Game Developer Design, Production, and Industry Awareness. - Thorn, Alan (linkedin.com, 2021)
Prepare for the sections of the Unity Certified Associate: Game Developer exam that deal with game design, collaboration, industry awareness, and mobile development.